The Relationship Between Social Risks and the Mental Health of School-Age Children in Primary Care - Spencer, Andrea E. (Acad Pediatr, 2019)
BACKGROUND AND OBJECTIVES: The study’s goal was to measure the association between social risks and the mental health of school-age children in primary care. METHODS: We conducted a cross-sectional study in an urban safety-net hospital-based pediatric clinic using data collected from two standard screening tools administered at well child care visits for children age 6–11. Psychosocial dysfunction was measured with the Pediatric Symptom Checklist-17 (PSC-17) and six social risks (caregiver education, employment, child care, housing, food security, and household heat) were measured with the WE CARE screener. Multivariable linear and logistic regression analyses were conducted to measure the association between scores while controlling for sociodemographic characteristics. RESULTS: Among N=943 patients, cumulative social risks were significantly associated with a positive PSC-17 total score (Adjusted Odds Ratio [aOR] 1.2; 95% CI [1.1–1.5]; p=0.02), indicating psychosocial dysfunction. Children with ≥3 social risks were 2.4 times more likely to have a positive PSC-17 total score compared to children with <3 social risks (95% CI [1.5–3.9]; p<0.001). Of the individual social risks measured, only food insecurity significantly predicted a positive PSC-17 total score (aOR 1.9; 95% CI [1.1–3.2]; p=0.02) and attention score (aOR 1.9; 95% CI [1.1–3.4]; p=0.03). CONCLUSION: Number of risks on a social risk screener was associated with psychosocial dysfunction in school-age children. Food insecurity was the only individual risk associated with psychosocial dysfunction, in particular attention problems. Screening tools for social risks could be used to identify at-risk children whose mental health may be adversely impacted by their social conditions.